Encuesta Nacional de Salud y Nutrición 2023: metodología y avances de la Ensanut Continua 2020-2024. - Romero-Martínez, Martín; Shamah-Levy, Teresa; Barrientos-Gutiérrez, Tonatiuh; Cuevas-Nasu, Lucía; Bautista-Arredondo, Sergio; Colchero, M. Arantxa; Gaona-Pineda, Elsa B.; Martínez-Barnetche, Jesús; Alpuche-Aranda, Celia; Gómez-Acosta, Luz M.; Mendoza-Alvarado, Laura R.; Rivera-Dommarco, Juan; et al. (Salud Pública de México)
Objective. To present the methodology of the Encuesta Nacional de Salud y Nutrición 2023 (Ensanut 2023) and to describe the inference procedures to combine the information collected by the Ensanut Continua 2020-2024. Materials and methods. Ensanut 2023 is the fourth survey in the Ensanut Continua 2020-2024 series. The scope of the Ensanut 2023 is described together with its procedures for sampling, estimation, measurement, and logistic organiza- tion. In addition, the basic estimation procedure to analyze the union of the Ensanut Continua 2020-2024 surveys are discussed. Results. The Ensanut 2023 will obtain at the national level, at least 11 720 complete household inter- views and 13 378 complete adult questionnaires. The union of the Ensanut Continua 2020-2023 will allow, in general, to estimate prevalences greater than 20% with tolerable reliability at the state level. Conclusions. The analysis of the union of the Ensanut Continua 2020-2023 will start the generation of national and state estimates on health and nutrition status of Mexican population.